Images and spectra of time-dependent two-component advective flow in presence of outflows. Issue 3 (3rd May 2018) - Chatterjee, Arka; Chakrabarti, Sandip K; Ghosh, Himadri; Garain, Sudip K
ABSTRACT: Two-component advective flow (TCAF) successfully explains the spectral and temporal properties of outbursting or persistent sources. Images of static TCAF with Compton cloud or centrifugal pressure supported boundary layer due to gravitational bending of photons have been studied before. In this paper, we study time-dependent images of advective flows around a Schwarzschild black hole, which include cooling effects due to Comptonization of soft photons from Keplerian discs as well as the self-consistently produced jets and outflows. We show the overall image of the disc-jet system after convolving with a typical beamwidth. A long exposure image with time-dependent system need not to show the black hole horizon conspicuously, unless one is looking at a soft state with no jet or the system along the jet axis. Assuming these disc-jet configurations are relevant to radio emitting systems also, our results would be useful to look for event horizons in high accretion rate supermassive black holes in Seyfert galaxies, RL Quasars.